Constructing Sexism: Sociocultural Dynamics in the Mandar Community - Muhammad Kamal; Orindevisa Orindevisa (LPPM IAIN Parepare, 2024)
This study examines the socio-cultural construction of sexism within the Mandar community, a society in Sulawesi Barat known for its rich traditions and historical significance. It aims to uncover how gender dynamics are internalized and reproduced, focusing on the intersection of traditional values, modernity, and global influences. The research specifically explores the role of sibaliparri, a traditional gender relation system, in shaping societal norms and expectations. Using a qualitative field research approach, data was gathered through direct observation and in-depth interactions with local stakeholders. This method provided a detailed understanding of how sexism manifests within the social fabric of Mandar. The findings show that sexism positions men as dominant and women as subordinate, leading to unequal opportunities in education, employment, and decision-making. These disparities are further amplified by modern influences, particularly through cultural shifts introduced by social media. By contextualizing sexism within the unique socio-cultural framework of Mandar, this research offers an original perspective on gender inequality. It highlights the tension between preserving traditional values and adapting to modern influences, emphasizing the need for culturally sensitive strategies to address these disparities. The study underscores the importance of inclusive communication practices and tailored interventions to promote gender equity in the Mandar community and beyond.